Pertanggungjawabaan Pidana Selebgram Dalam mempromosikan Judi Menurut UU ITE - Zega, Ventry Faomassi; Aruan, Hernita; Purba, Roni Dear A; Rumapea, Mazmur Septian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The development of technology in Indonesia is growing rapidly, the function of finding information is changing day by day to now being used as a way of livelihood. The development of technology is one of the driving factors for crime by using the internet as a means. Various crimes or criminal acts related to electronic transaction information or regulating users of information and electronic transactions carried out with electronic media are regulated in the ITE law. So that the formulation of the problem taken is how the criminal regulation of gambling in Indonesia according to the Criminal Code is and how is criminal responsibility in promoting gambling according to the ITE Law. The purpose of this study is to determine the criminal regulation of gambling in Indonesia according to the Criminal Code and accountability in promoting gambling according to the ITE Law. The results of the study stated that the crime of online gambling is specifically regulated in Article 27 paragraph 2 of Law Number 11 Year 2008 regarding information and in Article 303 of the Criminal Code concerning ordinary gambling.